A NEW SPECIES OF TEMNOCEPHALA BLANCHARD (PLATYHELMINTHES, TEMNOCEPHALIDA) ECTOSYMBIONT ON DILOCARCINUS SEPTEMDENTATUS (DECAPODA, TRICHODACTYLIDAE) FROM THE BRAZILIAN AMAZONIA - A. Seixas, Samantha (2011)
Temnocephala longivaginata sp. n., an ectosymbiont on Dilocarcinus septemdentatus (Herbst, 1783), is described from crabs in the State of Pará, Brazilian Amazonia. Fifty crabs were collected from the Rio Peixe-Boi, Municipality of Peixe-Boi. Dilocarcinus septemdentatus is the type host of Temnocephala microdactyla Monticelli, 1903, a species with a precarious original description, but redescribed on two other occasions from different hosts: Sylviocarcinus australis Magalhães & Türkay, 1996 and Dilocarcinus pagei Stimpson, 1861. The new species is most similar to Temnocephala pignalberiae Dioni, 1967, but differs by having the following characters: 1. cirrus with a circle of sclerites in the distal portion of the introvert, followed by a smooth portion (without spines or ridges); 2. proximal, inner portion of the introvert with longitudinal ridges; 3. vesicula 'intermedia' long, replacing the seminal receptacles; 4. vagina long, with a widening of its distal portion, near the asymmetrical vaginal sphincter; and 5. small and 'shoe sole' shaped dorsolateral 'excretory' syncytial epidermal plates. Prior to the present study, all species of Temnocephala were shown to have the cirrus' introvert either smooth or with spines. Ridges in the inner wall of the introvert and a circle of sclerites are here recorded for the first time in Temnocephalidae.